Long-term trends in human fatalities from human–elephant conflict in Chhattisgarh, India - Kalpana Roy; Ramesh Kumar Pandey; N. G. Athira; Ananya Dutta; Dheeraj Mittal; Parag Nigam; Anukul Nath; Bilal Habib (Scientific Reports)
Abstract Human-elephant conflict poses a major challenge to both wildlife conservation and human livelihoods across Asia. These conflicts often occur due to habitat fragmentation, agricultural expansion, and the depletion of natural food resources, increasing the frequency of interactions between elephants and humans. We investigated human fatalities and injuries over 23 years (2000–2023) in Chhattisgarh, India, focusing on temporal variations and the underlying drivers of conflict. Data collected from 19 forest divisions revealed a total of 828 incidents, including 737 human fatalities and 91 injuries, with Jashpur, Dharamjaigarh and Surajpur, emerging with the highest concentration of incidents. Most of these conflict incidents occurred during the monsoon. Conflict incidents are significantly influenced by proximity to natural and human-modified landscape features, with high-conflict zones near forest edges. The frequency of conflict incidents decreased with increasing distance from roads, crop fields, and built-up areas. Additionally, conflict incidents show a decreasing trend in areas with larger forest patches. Village-level analysis revealed that high-conflict areas have higher forest cover (~ 75%) and lower crop cover (< 25%). Prioritizing high-conflict villages, safeguarding elephant corridors, and implementing localized conflict mitigation measures in high-risk zones are essential to address the escalating human-elephant conflict (HEC) challenges in Chhattisgarh.